1972
DOI: 10.1039/dt9720001337
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterisation, and europium-151 Mössbauer spectra of some carbides, nitrides, nitride-carbides, cyanides, and thiocyanates of europium

Abstract: The reaction of europium metal with HCN and (CN), at elevated temperatures has been shown to yield Eu&, EuC,, and compounds of the type EuN, C, .X-Ray parameters for these phases are reported and they are shown by 151Eu Mossbauer spectroscopy to be band systems. EuN is shown to be ionic and to contain Eu3+ ions. The reactions in liquid NH, of europium with HCN, C2H2, and NH,SCN have been shown to produce europium(l1) and europium(lii) cyanide, europium(l1i) acetylide, and europium(l1i) thiocyanate respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

1972
1972
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
1
1
1
Order By: Relevance
“…In this respect, it is important to mention that Mössbauer measurements reported on previous EuC 2 samples revealed a very broad line width (Γ = 6 mm/s), which is nearly by a factor of 2 larger than that obtained for our sample. This reflects a considerable inhomogeneity of those samples.…”
Section: Resultscontrasting
confidence: 68%
See 2 more Smart Citations
“…In this respect, it is important to mention that Mössbauer measurements reported on previous EuC 2 samples revealed a very broad line width (Γ = 6 mm/s), which is nearly by a factor of 2 larger than that obtained for our sample. This reflects a considerable inhomogeneity of those samples.…”
Section: Resultscontrasting
confidence: 68%
“…9 As the reported unit-cell volume of EuC 2 is much larger than those of the other RE 3þ dicarbides, it was concluded that Eu 2þ ions were present and that the carbide was wholly ionic. 151 Eu M€ ossbauer spectra corroborated these assumptions, 10 although the reported lattice parameters of the sample under investigation differed largely from those reported earlier. 8 In the most recent investigation 11 of EuC 2 , a sample was synthesized with lattice parameters quite similar to those reported in the first work on EuC 2 .…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation